2014
DOI: 10.1017/jfm.2014.351
|View full text |Cite
|
Sign up to set email alerts
|

Shear-imposed falling film

Abstract: The study of a film falling down an inclined plane is revisited in the presence of imposed shear stress. Earlier studies regarding this topic (Smith, on the basis of a low Reynolds number, are extended up to moderate values of the Reynolds number. The mechanism of the primary instability is provided under the framework of a two-wave structure, which is normally a combination of kinematic and dynamic waves. In general, the primary instability appears when the kinematic wave speed exceeds the speed of dynamic wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 38 publications
6
36
0
Order By: Relevance
“…A profile initiated by h l = h 3 (figures [16][17][18][19] produces an undercompressive front at Re ⇤ = 0, also reported by Levy and Shearer [12]. We observe commonality of solution exhibited by changes in initial profile with equivalent boundary conditions developing into identically shaped wave structures.…”
Section: Formation Of New Frontssupporting
confidence: 76%
See 3 more Smart Citations
“…A profile initiated by h l = h 3 (figures [16][17][18][19] produces an undercompressive front at Re ⇤ = 0, also reported by Levy and Shearer [12]. We observe commonality of solution exhibited by changes in initial profile with equivalent boundary conditions developing into identically shaped wave structures.…”
Section: Formation Of New Frontssupporting
confidence: 76%
“…These capillary ripples are mesh-independent, indicating this is a model feature. They are also present in profiles obtained in other numerical studies which include the e↵ects of inertia [19], as well as observed in experimental work by Kofman et al [10]. Further investigations were carried out by varying the surface shear.…”
Section: Smoothing E↵ects Of Inertiasupporting
confidence: 66%
See 2 more Smart Citations
“…The mechanism of primary instability for the surface wave was nicely addressed by Smith when additional constant shear stress is exerted at the free surface. The model proposed by Smith was further revisited by Samanta to take into account the nonlinear inertial effect on the traveling wave solutions. It was reported that the surface instability exclusively occurs due to the competition between the kinematic wave and the dynamic wave.…”
Section: Introductionmentioning
confidence: 99%